INITIAL SCREENING OF CRITICAL SUCCESS FACTORS FOR GREEN, LEAN AND SIX SIGMA IMPLEMENTATION IN PAKISTANI SMALL AND MEDIUM ENTERPRISES - Wassan, Rano Khan; Shaikh, Shakeel Ahmed; Shaikh, Imran Khan; Memon, Muhammad Saad; Abdul Rahman; Shah, Syed Feroz Hussain (Journal of Applied Engineering Science, 2022)
It is believed that implementation of green, lean and six sigma (GLSS) practices in SMEs is important to achieve sustainable growth likewise large scale industries. Pakistan is a developing country and its economic development is heavily dependent over the existence and growth of SMEs. The aim of this study is to identify and rank the major critical success factors (CSFs) that will affect GLSS practices implementation in Pakistani SMEs. List of sixteen CSFs is developed based on the available literature and with the consultation of experts. Structured interviews are conducted from the academic and field experts to collect the data. Later on, data is statistically analyzed to rank the CSFs of GLSS implementation in SMEs. Top seven CSFs that achieved above 70% agreement by the experts are Management participation and support, Training and education, Leadership for GLSS, Legislation, Understanding GLSS methodologies, Organizational infrastructure and Technology up gradation in Pakistani SMEs. This study significantly lessens the implementation troubles and will assist in conducting empirical studies in SMEs by considering CSFs in Pakistani context.